Decision Making Style of Higher Secondary School Teachers - P. , Senthamizh; J. , Vigneshwari (International Journal of Psychosocial Rehabilitation, 2020)
Decision-making is the cognitive process involving information search, evaluation, judgement, problem-solving, and responses to a set of motivational forces that determine the manner in which decisions are made. A decision is a result of making a judgment or reaching a conclusion. The progress of making a nation depends to a large extent on individuals who can lead and guide their fellow men. This study has been undertaken to examine the decision-making style of headmistresses, to evaluate teachers in terms of levels of morale, and to try to explore whether there exists a relationship between the dimension of decision-making style and teacher morale.